2020
DOI: 10.1371/journal.pone.0229161
|View full text |Cite
|
Sign up to set email alerts
|

Measuring objectification through the Body Inversion Paradigm: Methodological issues

Abstract: Objectification occurs when a person is perceived and/or treated like an object. With the present work, we overview the available measures of objectification and present a series of studies aimed at investigating the validity of the task of inverted body recognition proposed by Bernard and colleagues (2012), which might potentially be a useful cognitive measure of objectification. We conducted three studies. Study 1 (N = 101) is a direct replication of Bernard et al.'s study: participants were presented with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…For example, other-objectification has been assessed using the body inversion paradigm that asks participants to identify upright and inverted images of sexualized and non-sexualized men and women (e.g., Bernard et al, 2012). Measures that assess the accuracy or speed of implicit associations (that pair pictures of women with words representing the categories of human, e.g., “culture,” vs. animal, e.g., “snout”; Puvia & Vaes, 2012) are also increasingly common, and a growing body of evidence shows that these findings are well replicated (e.g., Zogmaister et al, 2020). Of note, a small body of literature exploring implicit self-objectification also exists (see Dryden & Anderson, 2019; Morris et al, 2014).…”
Section: Objectification Theorymentioning
confidence: 99%
“…For example, other-objectification has been assessed using the body inversion paradigm that asks participants to identify upright and inverted images of sexualized and non-sexualized men and women (e.g., Bernard et al, 2012). Measures that assess the accuracy or speed of implicit associations (that pair pictures of women with words representing the categories of human, e.g., “culture,” vs. animal, e.g., “snout”; Puvia & Vaes, 2012) are also increasingly common, and a growing body of evidence shows that these findings are well replicated (e.g., Zogmaister et al, 2020). Of note, a small body of literature exploring implicit self-objectification also exists (see Dryden & Anderson, 2019; Morris et al, 2014).…”
Section: Objectification Theorymentioning
confidence: 99%
“…Previous studies have found an effect of gender of the stimuli with an absence of a BIE with sexualised female bodies, which they interpreted as showing that female bodies are less configurally processed or “objectified” [e.g., 22 ]. However, cautions have been raised such as the task being mirror reversal rather than visual processing of bodies [see 23 , 24 ]. More recently, Cazzato et al [ 25 ] found no effect of participant gender and found BIEs for both female and male stimuli, but with better processing of inverted male bodies.…”
Section: Discussionmentioning
confidence: 99%
“…This study has been questioned due to the use of non-standardized and controlled target stimuli. Indeed, the original stimuli seemed to differ in the amount of asymmetry in body postures not only between male and female targets, but also between the inverted and upright female targets influencing the outcome of the experiment in the expected direction (Schmidt & Kistemaker, 2015;Tarr, 2013;Zogmaister et al, 2020). Even though the sexualized body inversion effect has been replicated with other stimuli, these debates could be avoided introducing a set of standardized pictorial stimuli.…”
Section: Existing Stimulimentioning
confidence: 99%